PENGARUH PERLAKUAN AWAL TERHADAP BENIH TOMAT (LYCOPERSICON ESCULENTUM MILL.) - RAHMANSYAH, MAMAN (BERITA BIOLOGI, 1989)
MAMAN RAHMANSYAH,1978.Effect of preconditioning treatments on tomato seeds.Berita Biologi 3(9): 473-4 75. The study the effect of preconditioning treatments for tomato seeds on plant growth and production,five thousand tomato seeds were slowly rehydrated from 6 to 12% moisture content.The treated seeds were sown on moist straw paper at low (26°-28°C)and high (26°- 36°C fluctuated temperatures,others were planted after storage for 48 and 60 hours in the in-cubator (40 C).The germination percentages of seeds,pollen fertility, the percentage of fruits developed, the average weight of fruit and the weight of 1000 seeds were evaluated.Plants derived from rehydrating seeds and stored for 48 hours at 40°C gave the best performance on their germination (more than 90%),pollen fertility (95%) and also the highest total fruits harvested but not on fruit and seed weights.The best result of seed treatment were 12% of moisture content and its were stored for 48 hours at 40°C